The Health Literacy Questionnaire: Initial Validity Testing in a Norwegian Sample - Kristin Hjorthaug Urstad; Randi Andenaes; Astrid K. Wahl; Lisbeth G. Kvarme; Sølvi Helseth; Torbjørn Moum (SLACK Incorporated, 2020)
Background: The Health Literacy Questionnaire (HLQ) is a multidimensional generic questionnaire developed to capture a wide range of health literacy needs. There is a need for validation evidence for the Norwegian version of the HLQ (N-HLQ). Objective: The present study tested an initial version of the Norwegian HLQ by exploring its utility and construct validity among a group of nursing students. Methods: A pre-test survey was performed in participants (N = 18) who were asked to consider every item in the N-HLQ (44 items across nine scales). The N-HLQ was then administered to 368 respondents. Scale consistency was identified and extracted in a series of factor analyses (principal component analysis [PCA] with oblimin rotation) demanding a nine-dimension solution performed on randomly drawn 50% of the samples obtained by bootstrapping. Correlations between the nine factors obtained in the 13-factor PCA and the scale scores computed by the scale scoring syntaxes provided by the authors of the original HLQ were estimated. Key Results: The pre-test survey did not result in the need to rephrase items. The internal consistency of the nine HLQ scales was high, ranging from 0.81 to 0.72. The best fit for reproduction of the scales from the original HLQ was found for these dimensions: "1. feeling understood and supported by health care providers," "2. having sufficient information to manage my health," and "3. actively managing my health." For the dimensions "7. navigating in the healthcare system" and "8. ability to find good health information," a rather high degree of overlap was found, as indicated by relatively low differences between mean highest correlations and mean next-highest correlations. Conclusions: Despite some possible overlap between dimensions 7 and 8, the N-HLQ appeared relatively robust. Thus, this study's results contribute to the evidence validation base for the N-HLQ in Norwegian populations.